Prognostic significance of galectin‐3 expression in patients with resected NSCLC treated with platinum‐based adjuvant chemotherapy. Issue 10 (1st April 2021) - Kusuhara, Seiichiro; Igawa, Satoshi; Ichinoe, Masaaki; Nagashio, Ryo; Kuchitsu, Yuki; Hiyoshi, Yasuhiro; Shiomi, Kazu; Murakumo, Yoshiki; Saegusa, Makoto; Satoh, Yukitoshi; Sato, Yuichi; Naoki, Katsuhiko
Abstract: Background: Galectin‐3 (GAL3), a protein encoded by the LGALS3 gene, plays diverse roles in cancer initiation, progression, and drug resistance. Accordingly, high GAL3 expression in tumor cells is associated with poor prognosis in non‐small cell lung cancer (NSCLC). However, the prognostic impact of GAL3 expression on patients with resected NSCLC receiving platinum‐based adjuvant chemotherapy (AC) remains unclear. This study aimed to determine the prognostic significance of GAL3 expression in NSCLC patients receiving platinum‐based AC. Methods: The study included 111 patients with completely resected stages II and IIIA NSCLC who were receiving platinum‐based AC. GAL3 expression in cancer cells was evaluated immunohistochemically according to H‐score ("histo score), with a score of ≥170 considered as high expression. The correlation of GAL3 expression with clinicopathological characteristics and survival was subsequently evaluated. Results: In survival analysis, GAL3 expression was significantly associated with recurrence‐free survival (RFS) and overall survival (OS). In multivariate analysis, GAL3 expression was an independent predictive factor of RFS rather than OS. Conclusions: GAL3 expression is a reliable biomarker to predict the prognosis of completely resected NSCLC patients receiving platinum‐based AC. Abstract : High galectin‐3 expression is associated with poor prognosis in patients with NSCLC. Thus, galectin‐3 expression is a reliable marker in predicting clinical outcomes in patients with completely resected NSCLC treated with platinum‐based adjuvant chemotherapy. This study provides a further understanding of the tumorigenesis and biology of NSCLC, which might be useful in detecting novel prognostic markers or therapeutic targets in completely resected stages II and IIIA NSCLC receiving platinum‐based AC for improving survival outcomes.